2002
DOI: 10.1046/j.1471-4159.2002.00820.x
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine transport function is elevated in cocaine users

Abstract: Dopaminergic transmission has been suggested to be a primary mechanism mediating reinforcement, withdrawal and craving associated with psychostimulant addiction. Pyschostimulants attenuate dopamine transporter (DAT) clearance efficiency, resulting in a net increase in synaptic dopamine levels. Re-uptake rate is determined by the number of functional DAT molecules at the membrane surface. Previous in vivo imaging studies in humans and in vitro studies in postmortem human brain have demonstrated that chronic coc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
102
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(114 citation statements)
references
References 44 publications
12
102
0
Order By: Relevance
“…Nevertheless, what we were able to ascertain about the regulatory properties of the Int8-VNTR domain clearly suggests a mechanism by which this polymorphism can be associated with cocaine abuse by altering the tissue-specific or stimulusinducible expression of the DAT1 gene. A previous study investigating the effect of cocaine abuse in the postmortem human brain demonstrated that, in cocaine users, DAT1 levels and DA uptake were elevated in the ventral striatum when compared with control subjects, providing further evidence of adaptation in DA uptake after chronic cocaine exposure (33).…”
Section: Discussionmentioning
confidence: 71%
“…Nevertheless, what we were able to ascertain about the regulatory properties of the Int8-VNTR domain clearly suggests a mechanism by which this polymorphism can be associated with cocaine abuse by altering the tissue-specific or stimulusinducible expression of the DAT1 gene. A previous study investigating the effect of cocaine abuse in the postmortem human brain demonstrated that, in cocaine users, DAT1 levels and DA uptake were elevated in the ventral striatum when compared with control subjects, providing further evidence of adaptation in DA uptake after chronic cocaine exposure (33).…”
Section: Discussionmentioning
confidence: 71%
“…Specifically, DAT levels were found to increase, decrease, or stay unchanged in post mortem examinations of the brains of cocaine addicts by different researchers (Little et al, 1998a(Little et al, ,b, 1999Malison et al, 1998;Mash et al, 2002;Hitri et al, 1994;Hurd and Herkenham, 1993;Wilson et al, 1996). Some of this variability can be accounted for by the different procedures and ligands used by the different researchers.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Mash et al, (2002) observed directionally opposite changes in two different populations of cocaine addicts. Moreover, all of the studies cited above were conducted post mortem, where the length of withdrawal from cocaine, if any, is unknown, as is the cause of death.…”
Section: Discussionmentioning
confidence: 99%
“…While genetic differences in receptor number and binding are likely to occur, there is also evidence that environmental effects can play a significant role. Chronic cocaine users have altered regional density of several neurotransmitter receptors and monoamine transporters compared to non-cocaine users [94][95][96][97][98]. This group has suggested that these changes increase the susceptibility of chronic users to severe cocaine toxicity.…”
Section: Cocaine Toxicity: Tying Together Concentrations and Receptormentioning
confidence: 99%